RARE EARTH ELEMENTS IN APATITE: UPTAKE FROM H2O-BEARING PHOSPHATE-FLUORIDE MELTS AND THE ROLE OF VOLATILE COMPONENTS - Fleet M.E.; Pan Y. (My University, 1997)
The partitioning of rare earth elements (REEs) between fluorapatite (FAp) and H2O- bearing phosphate-fluoride melts has been studied at about 700 and 800°C and 0.10-0.15 GPa. REE uptake patterns, i.e., plots of D(REE:FAp/melt), are convex upwards and peak near Nd for single-REE substituted FAp at minor (0.03-0.25 wt% REE2O3) abundances, and binary (LREE + HREE)-substituted FAp, and hexa-REE-substituted FAp at minor to major (0.25-7.8 wt% REE2O3) abundances. Partition coefficients for minor abundances of REE and depolymerized phosphate melts are about 5, 8, and 1 for La, Nd, and Lu, respectively and broadly comparable to those for early fluorapatite in the fractionation of melts of basaltic composition. The Ca2 site exerts marked control on the selectivity of apatite for REE because it preferentially incorporates LREE and its effective size varies with substitution of the A-site volatile anion component (F, Cl, OH). Using simple crystal-chemical arguments, melt (or fluid)-normalized REE patterns are predicted to peak near Nd for fluorapatite and be more LREE-enriched for chlorapatite. These predictions are consistent with data from natural rocks and laboratory experiments. The wide variation in D(REE:apatite/melt) in nature (from <1 for whitlockite-bearing lunar rocks to about 100 for evolved alkalic rocks) is attributed largely to the influence of the volatile components.